The Dawn Sky "Kadzib": Quran and Hadith Perspective - Rojak, Encep Abdul; Hamdani, Fahmi Fatwa Rosyadi Satria; Irwansyah, Shindu; Syaban, Nisfa Lailah; Saifullah, M. Akmal (KnE Social Sciences, 2024)
The light of dawn Kazib is part of the study of Islamic Astronomy, especially in determining the start of Fajr. This article aims to explain the concept of Fajr Kazib from the perspective of the Quran and related hadiths. The method used in this study is qualitative with a thematic interpretation approach. Data collection were done using documentation studies, while data analysis were done using conceptual analysis. According to the results of this study, the Kazib light at dawn helps determine whether someone can eat when they are fasting. It is determined by the appearance of a white thread and a black thread, which distinguishes between the darkness of the night and the light of day. The study specification on Fajr Kazib is explained in the Hadith that there are two types of Fajr, first, which does not justify the Fajr prayer / it is permissible to eat Suhoor, and second, Fajr which permits Fajr prayer / it is not acceptable to eat Suhoor. Humans can know the signs of the two dawns from the phenomenon of the zodiac light in the eastern sky in the morning. Keywords: the Dawn Kazib, Islamic astronomy, Quran, Hadith